Розвиток комунікативних навичок у дітей із синдромом Дауна в умовах інклюзивної освіти в дошкільних навчальних закладах - Тертична, Н. А.; Дорохіна, А. О.; Tertychna, N. A.; Dorokhina, A. A. (Волинський національний університет імені Лесі Українки, 2012)
В статті проаналізовано результати дослідження особливостей формування комунікативних навичок у дітей дошкільного віку із синдромом Дауна в умовах інклюзивного навчання, які показали, що простежується стрімка тенденція підвищення рівня розвитку комунікативної сфери. Установлено позитивний взаємозв’язок між тривалістю виховання в інклюзивній групі та можливістю впливу на розвиток дітей з особливими потребами. The article deals with features of the effective communicative skills development of children with Down’s syndrome within the inclusive education in preschool institutions. The experimental psychopedagogic program brought its positive dynamics concerning the level of growth which is observed in communicative skills. Pronounced is the fact that the longer period of time a child with special needs has been visiting an inclusive group the better dynamic we can observe.
Development of Communicative Skills in the Children with Down’s Syndrome within the Inclusive Education in Preschool Institutions
Keywords: синдром Дауна; соціалізація; інклюзія; комунікативні навички; Down’s syndrome; socialization; inclusion; communicative skills